Back and beyond New Zealand painting for the young and curious - O'Brien, Gregory 1961- (Auckland University Press, 2008)
A painting can take you many places. It ca take you around the world, or it can take you around the country, city or neighbourhood you live in. It can also transport you back to the time of myths, legends and ancient history -- or it can take you way into the future.